Slovanska filologija v dialogu med Matijem Murkom in Jiříjem Polívko - Zelenková, Anna; Jensterle-Doležal, Alenka (Slavia Centralis, 2020)
Slavonic philology in Slovenian-Czech dialogue between M. Murko and J. Polívka at the turn of the 20th CenturyThe paper explores relations between two major Slavonic scholars in Europe at the turn of the 20th century: M. Murko (1861–1952) and J. Polívka (1858–1933). Based on a careful study of their correspondence, it particularises their fruitful collaboration in the area of Central Europe at the time when the advancement of Slavonic studies in the peripheral regions of the Hapsburg Empire brought together philological research and national revival as well as cultural and political ambitions. The relationship between the two men, as it was naturally fostered through the exchange of ideas and mutual inspirations, had a significant impact on their personal and professional careers. Their letters deal with the institutional history of Slavonic studies, referring to the newly-built Departments of Slavonic Studies in Prague and Vienna, and to the failed initiative to establish the Slovenian Faculty at Charles University, Prague.
Keywords: history of slavistics; correspondence between slavists; Matija Murko; Jiří Polívka; Slovene-Czech relations